Modeling the stress-strain state of a circular plate subject to general corrosion according to various models - Ovchinnikov, Ilya; Mavzovin, Vladimir (E3S web of conferences, 2021)
Quite a lot of works have been devoted to the problem of modeling the behavior of thin-walled structures exposed to an aggressive environment leading to corrosive wear of their surface. Researchers have proposed a fairly large set of models of corrosive wear, taking into account the influence of various factors on the kinetics of corrosion (time, material, temperature, the nature of the corrosive environment, the stress-strain state of the structure). Moreover, different authors often propose different models for the same conditions. In the article under consideration, a rather unique comparative study of three corrosion models proposed by different authors (Dolinsky V.M., Gutman E.M., Ovchinnikov I.G.) was carried out to simulate the behavior of the same circular plate subjected to the combined action of load and corrosion wear and tear. Moreover, the identification of the models, that is, the determination of the coefficients included in them, was carried out using the same experimental data. These models were then used to simulate the behavior of plates subject to corrosive wear under various loads. The results of numerical simulation were compared with experimental data obtained during testing of corrosive plates. Interestingly, in the models used, the effect of the stress state on the kinetics of corrosion was taken into account using different invariants of the stress state: the stress intensity in V.M. Dolinsky, medium voltage in the model of E.M. Gutman, and the specific energy in the model of I.G. Ovchinnikov. The analysis showed that the difference from the experiment when using the three models considered does not exceed 9.3%. The discrepancy between the results obtained using different models is also within the acceptable range, which suggests that all three models can be used to predict the behavior of plates under corrosive wear conditions. However, it is of interest to conduct research on the predictive capabilities of models on large forecast arms that go beyond the scope of experimental studies. At the same time, carrying out numerical experiments to simulate the behavior of complex structures in a stressed state and subject to corrosive wear, using several models that allow a good description of the experimental data and the most complete consideration of the operating conditions, makes it possible to obtain a more complete and versatile picture of what is happening in design processes, in comparison with the calculations performed according to one model, even if it describes the experimental data well.